Development Of Apparatus Competency In The Tourism And Cultural Department Of Trenggalek Regency (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2022)
The development of the globalization era requires human resources to develop and improve their potential and performance ability. This indicates the requirement of an apparatus, which has good competency to carry out authority. Trenggalek Regency is one of the Indonesian areas having amazing tourism potential, where a good competent apparatus is needed to manage and develop the tourism sector. Therefore, this study aims to determine and analyze the apparatus competency development of the Tourism and Culture Department in Trenggalek Regency, Indonesia. It also aims to determine the related inhibiting factors and the efforts provided to overcome them. In this study, a qualitative-descriptive method and an inductive approach were used, with interviews, observation, and documentation implemented for data collection. Data analysis was also carried performed through parameter reduction, presentation, verification, and conclusions. Based on the results, the implementation of the apparatus competency development was adequately performed at the Tourism and Culture Office of Trenggalek Regency. Irrespective of these conditions, some challenges were still observed, regarding the budget available for the developmental processes and the apparatus' lack of interest in activity participation. To overcome these challenges, interpersonal collaboration and participation in apparatus webinars were part of the efforts performed by the Department of Tourism and Culture.